Usulan Perancangan Tata Letak Fasilitas Produksi Dengan Metode BLOCPLAN Untuk Meningkatkan Produktivitas CV. Madu Apiari Mutiara - Adinda Siti Sarah; Annisa Oktaviana Putri; Raysha Putri Ramadhania; Saddam Cahya Maleon; Agung Prayudha Hidayat; Astiani Safitri (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
CV. Madu Apiari Mutiara is a company that operates in the field of derivative honey products such as pure honey, candy, soap, and health products such as propolis and other derivative products which have various shapes and compositions. This condition makes it necessary to have the most efficient spatial layout of work areas and production facilities in order to increase work morale and work productivity in terms of the layout of production facilities. The method used to solve this problem is the BLOCPLAN method. This method can solve facility layout problems in CV Madu Apiari Mutiara production houses with the level of close relationship, area requirements, taking into account the distance of material movement and final layout. The area on CV. Madu Apiari Mutiara is 100 m2, the total area requirement is 70.48 m2. There are 3 alternative layouts in the BLOCPLAN method, the proposed layout chosen is based on the R-Score value which is close to 1, namely the 2nd layout with a material movement distance efficiency of 8.1 meters or 20.9%.